Anisakis simplex Rudolphi ... - Luque, José L.; Muniz-Pereira, Luís C.; Siciliano, Salvatore; Siqueira, Liege R.; Oliveira, Magda S.; Vieira, Fabiano M. (Zenodo, 2010)
Anisakis simplex (Rudolphi) Feresa attenuata (Gray), stomach, São Paulo (Zerbini & Santos 1997). Phocoena dioptrica Lahille, stomach, Rio Grande do Sul (Pinedo et al. 2002). Pseudorca crassidens (Owen), stomach, Rio Grande do Sul (Andrade et al. 2001; Pinto et al. 2004). ... : Published as part of Luque, José L., Muniz-Pereira, Luís C., Siciliano, Salvatore, Siqueira, Liege R., Oliveira, Magda S. & Vieira, Fabiano M., 2010, Checklist of helminth parasites of cetaceans from Brazil, pp. 57-68 in Zootaxa 2548 on page 60, DOI: 10.5281/zenodo.196777 ...